2006
DOI: 10.2337/dc05-1788
|View full text |Cite
|
Sign up to set email alerts
|

Is Nonalbuminuric Renal Insufficiency in Type 2 Diabetes Related to an Increase in Intrarenal Vascular Disease?

Abstract: OBJECTIVE -To investigate the role of intrarenal vascular disease in the pathogenesis of nonalbuminuric renal insufficiency in type 2 diabetes.RESEARCH DESIGN AND METHODS -We studied 325 unselected clinic patients who had sufficient clinical and biochemical information to calculate an estimated glomerular filtration rate (eGFR) using the Modified Diet in Renal Disease six-variable formula, at least two estimations of urinary albumin excretion rates (AER), and a renal duplex scan to estimate the resistance inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
67
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 36 publications
14
67
1
4
Order By: Relevance
“…30 Recently, it has been noted that a substantial proportion of type 2 diabetes mellitus patients have renal insufficiency without albuminuria. 33,34 MacIsaac et al 34 showed that in type 2 diabetes mellitus patients with renal insufficiency, intra-renal resistive index obtained by Doppler ultrasound, which reflects intra-renal vascular injury, 35 was high regardless of the amount of albuminuria. Considering the results obtained in our studies, abnormal glucose metabolism/insulin resistance may induce tubulointerstitial injury and renal arterio-arteriolosclerosis even before the development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…30 Recently, it has been noted that a substantial proportion of type 2 diabetes mellitus patients have renal insufficiency without albuminuria. 33,34 MacIsaac et al 34 showed that in type 2 diabetes mellitus patients with renal insufficiency, intra-renal resistive index obtained by Doppler ultrasound, which reflects intra-renal vascular injury, 35 was high regardless of the amount of albuminuria. Considering the results obtained in our studies, abnormal glucose metabolism/insulin resistance may induce tubulointerstitial injury and renal arterio-arteriolosclerosis even before the development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a third of our patients with normal AER had mildly impaired renal function and 2% had impaired renal function. It has previously been shown that patients with type 2 diabetes and a reduced eGFR (calculated by MDRD6 formula) have a similar degree of intrarenal vascular damage irrespective of their AER status [23]. Likewise, a decline in renal function has been reported to be associated with an increase in carotid intimalmedial thickness and an increase in intrarenal arterial resistance index [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been variously reported that some diabetic patients have low renal function (typically expressed as estimated GFR [eGFR]) even in the absence of proteinuria [1][2][3][4][5]. However, little else is known about the risk factors or mechanisms associated with low eGFR in patients with either type 1 [5] or type 2 diabetes [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%